(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
In this paper, we investigate the impact of Smart Parking Systems (SPS) on urban mobility and the incorporation of technological innovations within the electric vehicle (EV) industry, focusing on Petrosani, Romania. As urban areas grapple with the challenges of rapid development, such as traffic congestion and inefficient use of parking spaces, SPS emerge as a crucial solution. This research presents a comprehensive analysis of Petrosani’s current traffic and parking conditions, leveraging public opinion surveys and traffic flow studies to propose an efficient integration of smart parking systems. The study reveals significant public support for SPS, highlighting a community eager to embrace solutions that enhance urban mobility, reduce environmental pollution, and improve the quality of urban life. Our findings suggest that adopting SPS in Petrosani could lead to more effective traffic management, better utilization of parking resources, and a shift towards sustainable urban development. The paper underscores the need for strategic planning and community involvement in transitioning towards smarter, more sustainable urban ecosystems, setting a precedent for similar initiatives in other cities. This work contributes to the discourse on sustainable urban planning, emphasizing the practical implications and benefits of intelligent parking solutions in enhancing urban mobility and environmental sustainability.